3D-architectured Pt-carbon electrodes for PEM fuel cells with tuned porosity and ionomer distribution-a micromanaged approach for improving activation, ohmic, and mass transport characteristics - Singh, Mayank U.; Mathew, Grigory; Kurungot, Sreekumar (ACS Applied Energy Materials, 2025)
The conventional catalyst layer in Proton Exchange Membrane Fuel Cells (PEMFCs) suffers the limitation of masked active sites, hindered proton transportation, excessive water clogging, and irregular ionomer distribution, resulting in an underutilized catalyst. To overcome these challenges, an innovative catalyst layer (CL) is constructed by aligning Vulcan carbon (VC) particles along a 3D carbon nitride interconnected network originating from a melamine sponge. This forms a robust scaffold rich in anchoring sites like sulfur and nitrogen for the Pt nanoparticle. The resultant 3D CL exhibits a doubled through-plane proton transport conductivity from 23 to 41 mS cm-1, delivering a 17.3% increase in the current density at 0.60 V compared to a conventional VC CL. This strategy enables enhanced ionomer incorporation, yielding a 19.60% enhancement in the ionomer coverage over the Pt without sacrificing the porosity, as verified by a mercury porosimeter. Kelvin probe force microscopy confirms a more uniform electron density across the 3D CL, in contrast to the traditional CL, suggesting uniform coverage. The advanced porosity and structure of the 3D CL allow the mass transport regions to shift to higher current densities, with an increase of 0.30 A cm-2 at 0.50 V compared to the VC CL. The improved ionomer coverage also demonstrates 19% lower voltage degradation at 0.80 A cm-2. Further, the impedance mapping across the entire current range graphically illustrates the 3D CL's advantage in the activation, Ohmic, and mass transport regions, showing a parabolic profile with a flattened bottom attributed to the reduced Ohmic resistance and its extension to delay the mass transport losses.
Keywords: 3D-structured catalyst layer; impedancemapping; ionomer coverage; low-temperature proton exchange membranefuel cell (LT-PEMFC); mercury porosimeter; proton resistance; triplephase boundary (TPB)